Turismo e desenvolvimento sustentáve l: o caso da Vila do Abraão - Oliveira, Sérgio Luis Paiva de (2006)
This present work has the objective to analyze the perspective of the sustainable development from the promotion of the tourism in Vila do Abraão, Ilha Grande. For this, was available the five dimensions of sustainable ¿ ecological, economic, social, space and cultural ¿ from the own words of the actors involved with the reality of the studied place. The research was applied as a study of case and had as objective to discuss the tourist¿s projects from Vila do Abraão, considered the viability of its sustainable. The discussion wasn¿t restricted to the economical aspects, but also the social-cultural and environment implications caused by tourism. The dialect method was used. Natives, residents, businesspeople, tourist, authorities, association representatives and others, were interviewed. They were questioned about negative and positive aspects from the local tourism, getting the chance to opinion. The segmented arguments of these actors made the base for new knowledge. This present dissertation arrived at some significant conclusions to the problems that represent barriers to the sustainable mentioned above. In conclusion, were set problems related to government body, whose political interest and insufficient recourses compromise the performance.